You are on page 1of 8

Mathematics 334 Designed by Peter Nield Notes by Katherine Daignault

Westwood High School Grade 9 Student

Rational Expressions
P(x )
Q(x ) P(x) and Q(x) are polynomials.
Q(x ) ≠ 0

STEPS (Simplifying):
1. Factor the numerator & denominator.
2. Make any restrictions.
3. Cancel out the factor common to both numerator & denominator.

EX. 1:
x +1
x + 3x + 2
2

x +1
= x ≠ −2 and − 1
(x + 2)(x + 1)
1
=
(x + 1)
EX. 2:
x 2 − 3x
x2 − 9
x( x − 3)
= x ≠ 3 and − 3
(x − 3)(x + 3)
x
=
(x + 3)
EX. 3:
2 x 2 + 14 x − 36
2x − 4

=
(
2 x 2 + 7 − 18 )
2( x − 2)

=
(
2 x 2 − 2 x + 9 x − 18 ) x≠2
2( x − 2 )
2( x − 2)( x + 9)
=
2( x − 2)
= (x + 9)

21
Mathematics 334 Designed by Peter Nield Notes by Katherine Daignault
Westwood High School Grade 9 Student
EX. 4:
2x 2 + 6x
2 x 2 − 18
2 x( x + 3)
=
2(x 2 − 9)
2 x( x + 3)
= x ≠ −3 and 3
2( x − 3)( x + 3)
x
=
(x − 3)
Can only be cancelled out if being multiplied with 2nd
term!!

22
Mathematics 334 Designed by Peter Nield Notes by Katherine Daignault
Westwood High School Grade 9 Student

Rational Expressions Multiplication


P(x ) R( x )

Q( x ) S ( x )
P(x), Q(x), R(x), S(x) are polynomials.
Q(x) & S(x) ≠ 0

STEPS:
1. Factor.
2. State restrictions.
3. Write as one expression.
4. Cancel out factors.

EX. 1:
y2 + y 1
×
y − 3 y +1
y ( y + 1) 1
= × y ≠ 3 and − 1
y −3 y +1
y ( y + 1)
=
( y − 3)( y + 1)
y
=
( y − 3)
EX. 2:
3a − 3b a 2
×
a a −b
3(a − b ) a(a )
= × a ≠ b and 0
a a−b
3(a − b )(a )(a )
=
(a )(a − b )
= 3a

23
Mathematics 334 Designed by Peter Nield Notes by Katherine Daignault
Westwood High School Grade 9 Student

EX. 3:
x 2 + 6x + 8 2x 2 + x
× 2
x+2 x + 4x + 4
x + 4x + 2x + 8
2
x(2 x + 1)
= × 2
x+2 x + 2x + 2x + 4
x ( x + 4 ) + 2( x + 4 ) x(2 x + 1)
= ×
x+2 x( x + 2 ) + 2( x + 2 )

=
(x + 2)(x + 4) × x(2 x + 1) x ≠ −2
x+2 (x + 2)(x + 2)
=
(x + 2)(x + 4)(x )(2 x + 1)
(x + 2)(x + 2)(x + 2)
x( x + 4 )(2 x + 1)
=
(x + 2)(x + 2)
x( x + 4 )(2 x + 1)
=
( x + 2 )2
EX. 4:
x 2 x + 10
×
x 2
+ 8 x + 15 x2
x 2( x + 5)
= × x ≠ −5, − 3 and 0
(x + 5)(x + 3) x(x )
=
(x )(2)(x + 5)
(x + 5)(x + 3)(x )(x )
2
=
(x )(x + 3)

24
Mathematics 334 Designed by Peter Nield Notes by Katherine Daignault
Westwood High School Grade 9 Student

Rational Expressions Division


P(x ) S (x )
÷
Q(x ) R( x )

Q(x), S(x), R(x) ≠ 0

STEPS:
1. Factor.
2. Restrict.
3. Flip 2nd fraction and change ÷ to × .
4. Restrict.
5. Multiply.

EX. 1:
x2 − y2
÷ (2 x + 2 y )
x− y

=
(x − y )(x + y ) ÷ 2(x + y ) x≠ y
(x − y )
=
(x − y )(x + y ) × 1 x ≠ −y
(x − y ) 2(x + y )

=
(x − y )(x + y )
(x − y )(2)(x + y )
1
=
2
EX. 2:
y2 + y
÷ ( y + 1)
y−2
y ( y + 1)
= ÷ ( y + 1) y≠2
y−2
y ( y + 1) 1
= × y ≠ −1
y − 2 ( y + 1)

=
( y )( y + 1)
( y − 2)( y + 1)
y
=
y−2

25
Mathematics 334 Designed by Peter Nield Notes by Katherine Daignault
Westwood High School Grade 9 Student

EX. 3:
2x − 4 y 20
÷
3 x + 6 5 x + 10
2( x − 2 y ) 20
= ÷ x ≠ −2
3( x + 2 ) 5( x + 2 )
2( x − 2 y ) 5( x + 2 )
= × x ≠ −2
3( x + 2 ) 20

=
(2)(x − 2 y )(5)(x + 2)
(3)(x + 2)(20)
=
(10)(x − 2 y )
(60)
=
(x − 2 y )
6
EX. 4:
2m 2 + 7 m − 15 9m 2 − 4
÷
m+5 3m + 2
=
(x + 5)(2m − 3) ÷ (3m − 2)(3m + 2) m ≠ −5 and −
2
m+5 3m + 2 3
=
(m + 5)(2m − 3) × 3m + 2 2
m ≠ −5, − , and
2
m+5 (3m − 2)(3m + 2) 3 3

=
(m + 5)(2m + 3)(3m + 2)
(m + 5)(3m − 2)(3m + 2)
=
(2m − 3)
(3m − 2)

26
Mathematics 334 Designed by Peter Nield Notes by Katherine Daignault
Westwood High School Grade 9 Student

Rational Expressions Addition & Subtraction


P(x ) S (x )
+ Q( x ), R( x ) ≠ 0
Q( x ) R( x )
P ( x )R( x ) + Q( x )S ( x )
=
Q( x )R (x )

a c ad + bc
+ =
b d bd

STEPS:
1. Factor.
2. Restrict.
3. Simplify.
4. Add/Subtract.
5. Factor, Simplify.

EX. 1:
3 3
+ x≠0
2 x 3x
3 1
= +
2x x
3x + 2 x
=
2 x( x )
5x
= 2
2x
5
=
2x
EX. 2:
a2 16

(a + 4) (a − 4)
a(a ) 16
= − a ≠ −4 and 4
(a + 4) (a − 4)
a 2 (a − 4 ) − 16(a + 4)
=
(a + 4)(a − 4)
a 3 − 4a 2 − 16a − 64
=
(a + 4)(a − 4)
a 2 (a − 4 ) − 16(a + 4)
=
(a + 4)(a − 4)
EX. 3:

27
Mathematics 334 Designed by Peter Nield Notes by Katherine Daignault
Westwood High School Grade 9 Student
x+2 x
− x ≠ 0 and − 1
x x +1

=
(x + 2)(x + 1) − x 2
x( x + 1)
x 2 + 3x + 2 − x 2
=
x( x + 1)
3x + 2
=
x( x + 1)

28